Percepción del posconflicto en Colombia: caso del alumnado de educación secundaria (2021)
After the 2016 Peace Agreement between the of the Republic of Colombia government and the FARC guerrilla, the Chair for Peace was implemented within the post-conflict consolidation policies. In order to know its impact on the post-conflict perception, we conducted a mixed quantitative investigation in which qualitative data are used to reinforce the results obtained with a Likerttype scale applied to a sample 793 high school students in Barranquilla and the metropolitan area. The results demonstrate that the post-conflict is perceived as a formally new stage, but the participants do not appreciate a difference regarding to what matters to them. The estrangement, the rhythms of change, the uncertainty, and the strategic ignorance are key to comprehend their response.